FUNCTIONAL AND MORPHOMETRIC EVALUATION OF PROSTATE MICROCIRCULATION FOLLOWING HIGH-INTENSITY FOCUSED ULTRASOUND THERAPY WITH ANDROGEN DEPRIVATION FOR PROSTATIC ADENOCARCINOMA - V. P. Levin; A. I. Neymark; I. V. Kachesov; S. M. Balakhnin; M. A. Bakarev (Сибирский научный медицинский журнал, 2019)
Objective. To evaluate morphometric and hemodynamic changes in the prostate microcirculation under high-intensity focused ultrasound therapy (HIFU) combining with androgen deprivation in prostate cancer patients with a focus on the treatment effect assessment. Material and methods. 119 patients with localized adenocarcinoma of the prostate (Т2а-сN0M0) were examined prior to HIFU ablation and 3 to 36 months following the treatment. Microvascular density in the prostate tissue and hemodynamic parameters recorded by laser Doppler flowmetry at the prostate projection area (PPA) of the skin were analyzed comparatively. Results and discussion. Successful HIFU ablation (recurrence free survival at 3-year follow-up period) was associated with higher pretreatment microvascular density in the prostate tumor tissue and with a marked reduction of this parameter in the areas of residual non-neoplastic parenchyma after the ablation, which was accompanied by a significant decrease in PPA microhemodynamics. A course of androgen deprivation administered 1-3 months prior to ablation contributed to a moderate pre-HIFU reduction of tumor vascularization and PPA microcirculation index. As compared to HIFU monotherapy, cooperative use of HIFU and androgen blockade was associated with a relative decrease in the number of microvessels in the areas of residual neoplastic and non-neoplastic parenchyma in cases with local recurrence. A substantial increase of PPA microcirculation indices 6 or more months after HIFU ablation was found to be strongly associated with prostate cancer local recurrence which suggests that laser Doppler flowmetry could be used in the complex monitoring of the outcome from HIFU therapy for prostatic adenocarcinoma.